The end of a spouse’s life from the perspective of canonical marriage law - Rakoczy, Bartosz (Studia Iuridica Toruniensia, 2024)
The end of the life of the spouse, as a legal event, is of significant importance in canon law. Indeed, the end of the life of the spouse in the case of a validly contracted and completed marriage is the only circumstance causing the termination of the marriage knot. Hence, the ecclesiastical legislator attaches considerable importance to the end of a spouse’s life. As has been proven from the point of view of canon law, the manner in which a spouse ends his or her life matters. This applies to the situation of spousal suicide. Although death by spousal suicide ends the marital knot, the surviving spouse cannot benefit from such a situation. Hence, the obstacle of spousal suicide has been established. The importance and significance of the end of a spouse’s life is of such significance that the ecclesiastical legislator, in case of doubt as to whether such an end has actually occurred, has provided for appropriate proceedings. These proceedings are initiated in the absence of an authentic secular or ecclesiastical document confirming the death of the spouse. A declaration by the diocesan bishop, issued after he has obtained moral certainty, replaces such a document. It should be noted that until such a declaration is issued, the surviving spouse is bound by the marriage bond.